New Publicness and Its Implication on Social Conflicts: The Relation between Local Community and the Gated Community in Sleman - Handoyo, Asmarawati; Hadna, Agus Heruanto; Ratminto, Ratminto (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2017)
This article discusses the rise of new public issues and their implication on social conflict inflicted by the rapid growth of gated community in Sleman District. These new public issues include economic problems, accessibility, social and environmental problems. Through the methods of observation and in-depth interview, it is found that the rise of the new public issues triggers conflicts when meeting two following requirements: (1) Both communities are unsuccessful in establishing an agreement to resolve new public issues, and (2) There is no local government intervention to overcome the new public issues of gated community. This article has two objectives: conceptually, it supports the new publicness theory stating that publicness may arise from the privacy sphere, while at the same time complete the fact that the rise of new public issues can cause social conflicts when meeting the two preconditions. Based on the findings in this study, two suggested recommendations include, first, both communities need to build intensive communication and create joint mechanism to avoid social conflict; second, the commitment and active role of Sleman government are required, particularly to eradicate the rents of licensing-bureaucracy and to improve close supervision in the field, so that new licensing processed will not instigate new public issues that can trigger social conflicts.